Millennial researchers in a metric-driven scholarly world: An international study. Issue 3 (27th May 2020) - Nicholas, David; Herman, Eti; Jamali, Hamid R; Abrizah, Abdullah; Boukacem-Zeghmouri, Cherifa; Xu, Jie; Rodríguez-Bravo, Blanca; Watkinson, Anthony; Polezhaeva, Tatiana; Świgon, Marzena
Abstract: The study Investigates the attitudes and practices of early career researchers (ECRs) in regard to citation-based metrics and altmetrics, providing the findings in the light of what might be expected of the millennial generation and in the context of what we already know about researchers in today's 'culture of counting' governed scholarly world. The data were gathered by means of an international survey, informed by a preceding, 3-year qualitative study of 120 ECRs from 7 countries, which obtained 1, 600 responses. The main conclusions are: 1, citation indicators play a central and multi-purpose role in scholarly communications; 2, altmetrics are not so popular or widely used, but ECRs are waking up to some of their merits, most notably, discovering the extent to which their papers obtain traction and monitoring impact; 3, there is a strong likelihood that ECRs are going to have to grapple with both citation-based metrics and altmetrics, mainly in order to demonstrate research impact; 4, the Chinese are the most metric using nation, largely because of governmental regulations.